Comparative Pharmacokinetics and Preliminary Pharmacodynamics Evaluation of Piscidin 1 Against PRV and PEDV in Rats - Lei, Zhixin; Liu, Qianying; Zhu, Qianqian; Yang, Bing; Khaliq, Haseeb; Sun, Ao; Qi, Yi; Moku, Gopi Krishna; Su, Yafan; Wang, Jiawei; Cao, Jiyue; He, Qigai (Frontiers in Chemistry, 2018)
Antimicrobial peptide (Piscidin-1) is an effective natural polypeptide, which has great influence and potential on porcine epidemic diarrhea virus (PEDV) and pseudorabies virus (PRV). As an alternative antibiotic substitute, Piscidin-1 was subjected for pharmacokinetics study with three administration routes (i.v, i.m and p.o) after a single dose of 2mg/kg in rats and preliminary pharmacodynamics including antiviral activity in cell against PEDV and PRV. Based on 50 percent tissue culture infective dose (TCID50), there were about 2% and 10% virus survived ratios for Piscidin-1 against PRV and PEDV, respectively. The plaque test showed 1 and 2μg/ml Piscidin-1 could eliminate 95% PRV and 85% PEDV, respectively. The main pharmacokinetics parameters of Cmax, AUC0-∞, Ke, t1/2, Tmax, MRT and Clb in plasma were not applicable value, 25.9 μg*h/ml, 0.041 h-1, 16.97 h, not available value, 22.77 h, 0.067 L/h*kg after i.v administration, 2.37 μg/ml, 18.95 μg*h/ml, 0.029 h-1, 23.50 h, 0.33 h, 30.12 h, 0.095 L/h*kg after i.m administration and 0.73 μg/ml, 9.63 μg*h/ml, 0.036 h-1, 19.46 h, 0.50 h, 26.76 h, 0.171 L/h*kg after p.o administration. The bioavailability values after i.m and p.o administrations were calculated as 73.17% and 37.18%, respectively. The i.m administration was selected for pharmacokinetics study in ileum content against PEDV. The main pharmacokinetic parameters of Cmax, AUC0-∞, Ke, t1/2, Tmax, MRT and Clb in ileum content were 1.67 μg/ml, 78.40 μg*h/ml, 0.034 h-1, 20.16 h, 8.12 h, 36.45 h, 0.026 L/h*kg. The Cmax values in plasma (2.37 μg/ml) and ileum content (1.67 μg/ml) were higher than the effective inhibitory concentration determined in the plaque test, and this indicates that Piscidin-1 might have effective inhibition effect against PRV and PEDV after administration of 2 mg/kg i.m. The results of this study represent the first investigations toward the pharmacokinetic characteristics of piscidin-1 in plasma upon three different administration routes, among which i.m. resulted in the highest bioavailability (73.17 %). Furthermore, the pharmacokinetics study of ileum content indicated Piscidin-1 might have good effect against PEDV and could be regarded as an alternative antibiotic in clinical veterinary in the future study.